Monocephalus Dipygus Dibrachius in a Shih Tzu Bitch: Monocephalus Dipygus Dibrachius em um Shih-Tzu de Dois Anos de Idade - Devit de Abreu, Juliana; Lopes Guarise, Raquel; Girolometto Fritsch, Deise; Barcelos Rocha, Mariana; Demarco, Janaina; Coelho, Juliana; Schuler Faccini, Leonardo; Coelho, Ana Carolina Barreto (Acta Scientiae Veterinariae, 2023)
Background: Congenital anomalies are structural, functional, or metabolic defects caused by a combination of environmental, genetic, or even iatrogenic factors. Genetic defects, which can be inherited, are more common in purebred dogs. Teratogenic factors such as radiation, toxins, chemical agents, infectious diseases, mechanical influences, drugs given to the mother, and nutrition can affect the litter during gestational development. The incomplete division of a fertilized egg results in monozygotic, conjoined or Siamese twins, which are animals with complete or incomplete duplications. This paper reports on an adult bitch with monocephalus dipygus dibrachius and the surgical procedures. Case: A 2-year-old female Shih Tzu weighing 5 kg was admitted to a veterinary clinic, presenting with swelling and myiasis near the anus and several development disorders, characterized by 2 pelvises, 2 anuses, 2 vulvas, 2 forelimbs and 6 hindlimbs. Her physiological parameters were otherwise normal. Only the dog’s myiasis was treated at this time due to the owner’s financial straits. After 5 months, the owner brought the bitch back to the veterinary clinic because the animal presented with fecaloma in 1 of the anuses. Radiography revealed numerous alterations: seven lumbar vertebrae with marked vertebral axis deviation, reduced disc space, as well as ankylosis and fused ventral spondylosis at L6 and L7. Two pelvises fused medially by the wings of the ileum, with slight deviation and thinning of pelvic bones. Four hip joints and medial joints with pelvic avulsion and bone remnants of the pelvic limbs. Acetabular tearing slightly flattened femoral head and thickened femoral neck. Caudal vertebrae and vertebral axis located in left pelvis. Left lateral patella inserted in the trochlear groove and lateral dislocation of right patella. Right patellofemoral joint with smooth surface, preserved intra-articular density and cranial displacement of the tibia relative to the femoral condyles (cranial cruciate ligament rupture). An ultrasound analysis revealed 2 bladders. Two months later surgery was performed due to recurrent complications. During laparotomy 2 uteruses, 2 bladders and bifurcation of the intestine were observed. Ovariosalpingohysterectomy was performed in both uterus and enterectomy of the problematic intestinal portion. After 2 days of the surgery, blood transfusion was performed. Two days after the transfusion, there was extravasation of yellow fluid from the surgical cut and abdominal palpation was indicative of bladder rupture, so the patient was sent to emergency surgery. Unilateral nephrectomy and ureterectomy, and ruptured bladder cystectomy were performed. The dog remained hospitalized for 24 days after surgery, before it was released. Discussion: The classification of conjoined twins is based on the location of the junction and the number of limbs. Monocephalus dipygus dibrachius was diagnosed based on the fact that the dog had 1 skull, 2 thoracic limbs and 4 pelvic limbs, as well as the corresponding genitourinary and gastrointestinal tract alterations. Imaging scans are extremely important for a proper diagnosis to ensure appropriate surgery planning. The bitch was the result of inbreeding between a male dog and its offspring, which probably contributed to this malformation. There are very few reports of surviving adult conjoined animals, and even fewer descriptions of successful surgical treatments. To the best of knowledge of the authors, there are no previous reports of a surviving adult dog suffering from this malformation. Keywords: conjoined twins, malformation, congenital anomaly, surgery. Título: Monocephalus dipygus dibrachius em cadela Shih Tzu Descritores: gêmeos conjugados, malformação, anomalia congênita, cirurgia.